HUBUNGAN ANTARA XEROSTOMIA DENGAN GENDER DAN USIA PADA KELOMPOK LANJUT USIA DI KOTA DUMAI - bakar, abu; Ningrum, Valendriyani (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2023)
Introduction: The elderly population is increasing both globally and nationally, including in Dumai City, Riau Province. The older they get, the more health problems they complain about, and xerostomia is one of the most common issues. There are only a few studies that examine the problem of xerostomia in the elderly. Therefore, the purpose of this study is to examine how xerostomia relates to gender, age, and overall health among elderly people in Dumai City, Riau Province. Methods: This study used a cross-sectional design approach. The survey included data on gender, age, and subjective assessment of xerostomia using the Summated Xerostomia Inventory in Indonesian (SXI-ID) questionnaire, consisting of 5 questions with answer options: never, rarely, sometimes, often, and always. In addition, the standard xerostomia question, "How often does the mouth feel dry?" has four answer options: never, sometimes, often, and always. Sampling was done by the accidental sampling technique; 247 respondents met the requirements and participated in the study completely. Results: The study showed that more respondents of the male gender (18.6 ± 2.7) suffered from xerostomia than women (17.4 ± 4.4), which was statistically significant (p<0.05). The results of the Spearman Rank correlation test between the age variable and the xerostomia condition showed statistically significant results (p<0.05), namely that the older the age, the greater the potential for xerostomia in the elderly. Conclusion: The incidence of xerostomia is more prevalent in men and as individuals age. Promotive and preventive efforts for the oral health of the elderly need to be strengthened to minimize oral health problems due to xerostomia.